Construction Contracting Business and Legal Principles, Second Edition - Bartholomew, Stewart (Open textbook library., 2002)
This introduction to construction contracting as it applies to typical, every-day situations explains “theoretical” ideas in terms of what really happens in practice. It emphasizes the more common case law holdings and industry customs that help avoid troublesome legal issues during the completion of a project. Instructors reviewing or adopting this book are encouraged to register at https://bit.ly/interest_construction_contracting Any derivatives of this work must comply with the use and attribution requirements of the Creative Commons license, and include the following statement, “This material was previously published by Pearson Education, Inc.” Construction Contracting, 2nd edition is an "out of print," rights-reverted book for which the author's estate has given permission for digitization and release under a CC BY NC SA 4.0 license. It was previously published in 2002 by Pearson ISBN 1-13-091055-4. The copyright page has been edited and graphics redrawn. A new cover, dedication, acknowledgements, how to adopt this book, and author biography have been added, and the table of contents has been revised. As the book has been reformatted, the original back of the book index is not included.